E essa vontade de virar imagem... as relações entre a beleza real e a beleza da moda (ModaPalavra e-periódico, 2010)
This work tries to elucidate the relationship between the “real beauty” and the “fashion beauty”, and which consequences this causes to the “individual at post-modern society” and “self-individual” relationships. Observations were taken with basis at Jean Baudrillard´ Simulacrum theory. Initially is presented a summary about Simulacrum theory, reality, hiperreality and theirs relation with beauty concepts nowadays. After it were analyzed six interviews with woman of different ages. These interviews object to perceive the means by fashion beauty concepts affects their lives. Was used the phenomenology method that was considered the best to work with qualitative data because it´s peculiar characteristic of management with relative and changeable “trues” and so the relativity of human been
Keywords: hiperreality; fashion; beauty